2020
DOI: 10.21203/rs.3.rs-98578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognosis Analysis of Patients with Pancreatic Neuroendocrine Tumors After Surgical Resection and the Application of Enucleation.

Abstract: Objective: To investigate the prognostic factors of patients with pancreatic neuroendocrine tumor (pNENs) after surgical resection, and to analyze the value of enucleation for pNETs without distant metastasis that are well-differentiated (G1) and have a diameter ≤ 4cm. Methods: Data from pNET patients undergoing surgical resection between 2004 and 2017 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan–Meier analysis and log-rank testing were used for the survival compa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Second, G3 neuroendocrine carcinomas are extremely rare and highly aggressive. [56][57][58] Therefore, findings in this study may not apply to all G3 cases. We also found that the prognostic value of our gene signature was diminished in G3 cases.…”
Section: Discussionmentioning
confidence: 86%
“…Second, G3 neuroendocrine carcinomas are extremely rare and highly aggressive. [56][57][58] Therefore, findings in this study may not apply to all G3 cases. We also found that the prognostic value of our gene signature was diminished in G3 cases.…”
Section: Discussionmentioning
confidence: 86%